Bipedicle flap for reconstruction of post-electric scalp burn defect - Paul, Kaushik; Sharma, Saurabh; Paul, Deepashree (International Surgery Journal, 2017)
High-tension electric calvarial burns are extremely rare and difficult to reconstruct. Invariably, these are third- or fourth-degree-deep burns involving the full thickness of the bone. Historically, these wounds have been treated conservatively, adding to morbidity and prolonged treatment. The patient with high-tension electric calvarial burns presented to us two days after the injury with subsequent loss of full thickness of parietal bone. The defect was covered with a local bipedicled scalp flap. The bipedicle flap provides a simple and reliable method of reconstruction of full thickness scalp defect.